Back analysis in rock engineering - Sakurai, Shunsuke, 1935- (Netherlands : CRC Press/Balkema, 2021)
'This book provides practicing engineers working in the field of design, construction and monitoring of rock structures such as tunnels and slopes with technical information on how to design, how to excavate and how to monitor the structures during their construction. Based on the long-term engineering experiences of the author, field measurements together with back analyses are presented as the most powerful tools in rock engineering practice. This book is the first to describe an observational method in rock engineering practice, which implies that the potential readers of this book must be practicing engineers working on rock engineering projects.'--
Includes bibliographical references and index.
Keywords: Rock mechanics; Geotechnical engineering